Dynamic changes in the transcriptional profile of subventricular zone-derived postnatally born neuroblasts - Khodosevich, Konstantin; Alfonso, Julieta; Monyer, Hannah (Mechanisms of development, 2013)
The subventricular zone (SVZ) of the lateral ventricles is a major neurogenic region in the postnatal mammalian brain. Thousands of neuroblasts are generated daily throughout the life of an animal. Newly born neuroblasts migrate via the rostral migratory stream (RMS) into the olfactory bulb where they mature into distinct neuronal subtypes. Neuroblasts exiting the SVZ retain the ability to proliferate, however, proliferation declines in the course of migration to the olfactory bulb. While migrating in the RMS, neuroblasts receive a plethora of stimuli that modify transcription according to the local microenvironment, and eventually modulate neuroblast migration. In the target area, the olfactory bulb, neuroblasts develop into mature neurons. In this review, we discuss dynamic changes of the transcriptome that occur during the “lifetime” of a neuroblast, thereby governing the activation or inhibition of distinct genes/pathways that are responsible for proliferation, migration and differentiation.
Available online 5 December 2012
Gesehen am 16.08.2018